অন্তর্যাত্রা: Tareque Masud Memorial and Cultural Center; Bhanga, Faridpur - Binte Kibria, Nafia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.